Diagnostic and therapeutic aspects of recurrent renal stone disease - Meyers, Anthony; Whalley, Natalie; Martins, Maria (African Journal of Nephrology, 2016)
Recurrent renal stones occur in 7.5% ofCaucasian men and 3% of all women. Even withincreasing urbanisation, renal calculi are reported inless than I% of black South African men and women. Four hundred recurrent stone formers were studied at the metabolic stone clinic using routine and special tests. The appropriate therapy for each subgroup is outlined and studies on various different treatments are presented. In addition, lithogenic risk factors were studied in normal black and white subjects and in black stone formers, in order to clarify the low incidence in the black population. Patients were classified according dietary andmetabolic lithogenic risk factors. 10% of stoneformers had pure dietary factors. The percentage ofstone formers in each of the various metabolicsubgroups was as follows: Renal hypercalciuria 12%, Absorptive hypercalciuria 10%, Mild metabolichyperoxaluria 20%, Hypocitraturia 50%. Successfultherapy in terms of preventing further stoneformation was reported using indapamide, calciumcarbonate and potassium citrate in renal hypercalciuria,mild metabolic hyperoxaluria and hypo-citraturia respectively. Black volunteer subjects hadsignificantly higher 24hr urinary sodium excretionand significantly lower 24hr urinary calcium, citrateand cystine excretion than white volunteer subjects. Twenty-four hours urinary values in black stoneformers were found to be approaching those levelsfound in white. As urbanisation occurs in the black population, the incidence of urolithiasis would be expected to increase. We conclude that a detailed metabolic work-up is essential in the elucidation of the various metabolic risk factors. in so-called "idiopathic" CaOx stone formers. It allows appropriate, specific and highly cost-effective therapy aimed at the prevention of recurrence. [Erratum appears in AJN, 2017; 20(1):200.]